Contemporary jewellery as affective experience : resisting biopolitics : an exegesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Fine Arts at Massey University, Wellington, New Zealand - Zellmer, Johanna (Massey University, 2024)
Through this creative, practice-led research I consider the affective aesthetic experience of contemporary jewellery as an interactive event of resistance. ‘Contemporary jewellery’ is a field of visual art practice distinct from commercial, fashion and costume jewellery. Its objects relate the body to the world through affective events, through which they may be considered as a mode of political intervention. As a jeweller, I am working in the space between craft and bioart, where materials are in a continuous visceral process of transformation. My project focusses on the making of collars and chokers out of used Illumina flow cells, waste products of the data collection technology known as DNA sequencing. Encircling and adorning a neck with these materials can create a significant affective experience. The human neck is a site of vulnerability and affect, where acts of power are displayed and experienced. Both jewellery and genomics are instruments of identity construction: the former a technology of the self and the latter a study of human bodies through scientific observation. Contemporary scholars such as Pravu Mazumdar, Elizabeth Povinelli, Stefan Muecke, and Thomas Lemke have undertaken extended research on such biopolitical conditioning. As an outcome of my craft training, my research inquiry is led by a creative, object-based practice. I have adopted the methodological framework known as speculative experimentation. This approach aligns with jewellery’s affective aesthetics through ‘critical hesitation, reflective questioning and thinking with unthinkable futures’. The experience of the resulting work can be destabilising and in turn creates hesitation, tension, and resistance. Artists and theorists Lauren Kalman, Tiffany Parbs, Agnieszka Wołodźko, and Renée Hoogland draw on these affective qualities of contemporary art and adornment. Informed by these key sources, this research project considers the agency of collars and chokers made from DNA sequencing tools as resistive ‘noise’ or irritants undermining the biopolitical standardisation of life and self. By fastening adornments firmly around the bare skin of a human neck, I am seeking to channel the haptic experience of these affective material objects into modes of resistance.
Figures are reused with permission.
Keywords: Jewelry making; Upcycling (Waste, etc.); Art objects; Wearable art; Political aspects; Resistance (Philosophy) in art; Affect (Psychology); contemporary jewellery; fine arts biopolitics; resistance; affective aesthetics; identity; ethics; application of DNA sequencing technology; 360602 Fine arts; 330310 Interaction and experience design